Real-Time Diagnostics on a QKD Link via QBER Time-Series Analysis - Georgios Maragkopoulos; Aikaterini Mandilara; Thomas Nikas; Dimitris Syvridis (Entropy)
The integration of QKD systems in metro optical networks raises challenges that cannot be fully resolved with current technological means. In this work, we devised a methodology for identifying different types of impairments for a QKD link embedded in a communication network. Identification occurs in real time using a supervised machine learning model designed for this purpose. The model takes only QBER and SKR time-series data as the input, making its applicability not restricted to any specific QKD protocol or system. The output of the model specifies the working conditions for the QKD link, which is information that can be valuable for users and key management systems.